Sibila: woman, music and tradition - ARENAS VANEGAS., ASTRID CAROLINA (Universidad Antonio Nariño, 2021)
Sibila: Woman, Music and Tradition it is a management and production project that seeks to recognize, value and make visible the contribution of women instrumentalists to the field of popular and traditional music in Colombia by carrying on a festival as a stage platform, allowing them to have a more comprehensive participation in the different dimensions of the musical field, being aware of the importance of their contribution to culture and empowering themselves with their own expressions and creations, and, in the case of the festival, showing them to the public through scenarios favorable to it.   Moreover, the festival has also established an academic strip: the conference-panel Women, Music and Tradition, which contributes to the transformation of collective thinking about the role of women in the social and cultural context, seeking also to change mentalities, stimulate reflections on professional development, sustainability, business creation, family influence, dependence on a cultural system that has been marked by different powers and whose access possibilities do not create equality, and a whole issue of inequality and lack of construction of spaces that strengthen the presence of women in the Colombian musical system.